Master Plan for Development and Support: Food Crops Commodities Based on Geographic Information Systems - Bella Rizky Yulianti; Suharno Suharno; Rakhmat Priyono (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
The agricultural sector has an essential role in the regional economy of the Demak Regency because the agricultural sector is the leading sector. The area of agricultural land in Demak Regency that continues to decrease requires detailed mapping portraits of each food crop commodity per sub-district. This study aims to analyze the leading food crop commodities in each sub-district, analyze the regional growth rate of food crop commodities, and map the food crop commodities developed in Demak Regency. Data analysis method using Location Quotient, Shift Share, Scalogram, and Geographic Information System. The results showed that rice and soybeans were the leading commodities with advanced and competitive growth rates in Demak Regency. The superior rice commodities in the districts are Bonang, Sayung, Karang Tengah, Wedung, and Mijen. Main Soybean Commodity in the District: Mijen. Map of the rice processing industry development in the districts: Dempet, Bonang, and Guntur. Map of soybean processing industry development in the districts: Guntur, Demak, and Mijen.